If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 176 + -16 = 0 Combine like terms: 176 + -16 = 160 160 = 0 Solving 160 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 1d-11=-1(2d-7) | | (x+3)(x-9)-(-5x-7)(x-2)= | | y-23+x=0 | | (6/5)*(x-7)=0 | | f(x)=-5x^2+60x-300 | | 12a+9ay-4y-3y^2= | | 3x/3=6/5 | | 5y+8x=-5 | | -3/5(5/8)x(3/4)=4/7(x/4-5/8) | | w+9=1 | | 7+4(8-5)= | | 9=2w-1 | | (x-y)dx+(x)dy=0 | | 1+2b-13=12-4b-2n | | 12=3(y-3)-6y | | 4=4.5x | | 6a+3a+3= | | 26.26=x+.04 | | (x-y)dx-(y)dy=0 | | f(3)=4.5x | | 26.26=x-.04 | | x^3-20*x^2+102*x-124=0 | | 24=(x+4)2 | | sec=6 | | -x/8=3/4x-1/8 | | 6x-4=3x+20 | | secx=6 | | .5*17x+6-7x-2=39 | | X=log(y-4)+3 | | 2/1-4/9 | | 1X+8R=35 | | 10/2.5 |